NFC and AR Interaction in Mobile Gaming - EINEBRANT, ERIK; Johansson, Tobias (My University, 2012)
This thesis explores how augmented reality and near field communication can be used as means of interaction in mobile gaming. In specific three prototype games have been developed and are analysed to find new design patterns which are supported by augmented reality and near field communication. The methods and the process of the development are described and analysed. Four interaction design patterns were discovered during the course of the project which helped to show that augmented reality and near field communication can be used for new forms of interaction in mobile games.
Keywords: Människa-datorinteraktion (interaktionsdesign); Informations- och kommunikationsteknik; Human Computer Interaction; Information & Communication Technology